Penegakan Hukum Terpadu Pada Tindak Pidana Pemilu: Analisis Peran Bawaslu Dalam Pemilihan Bupati dan Wakil Bupati Bungo 2024 - Ahmadi, Ahmadi; Al Idrusiah, Rahmi Hidayati; Maryani, Maryani; Farhan HR, Muhammad (PT. Riset Press International, 2025)
This study examines the role of the Election Supervisory Agency (Bawaslu) of Bungo Regency in handling criminal offenses in the 2024 Bungo Regent and Deputy Regent elections. This study uses an empirical juridical method with a case study approach to analyze the phenomena during the election process. The results show that Bawaslu maintains election integrity through prevention, supervision, and coordination with the Integrated Law Enforcement Center (Gakkumdu). However, Bawaslu faces various obstacles such as limited human resources, budget, infrastructure, geographical complexity, and low public legal awareness. Other obstacles also arise from multi-interpretable regulatory aspects and limited time to handle violations. The Revote (PSU) case at 21 polling stations (TPS) in Bungo Regency is clear evidence of the importance of adequate supervision so that the democratic process runs honestly, fairly, and transparently. This study emphasizes the need to optimize prevention strategies, utilize technology, strengthen human resource capacity, and increase public participation so that Bawaslu's role is more effective in creating quality and dignified elections.